Optimization of reaction variables in the sol-gel synthesis of Ni0.5Zn0.5Fe2O4 nanoparticles as a very fast adsorbent of methylene blue - Lotfi Ben Tahar; Mustafa Jaip Allah Abd Elmageed Abualreish; Adel Noubigh (Desalination and Water Treatment)
An optimization study for the sol-gel synthesis of Ni0.5Zn0.5Fe2O4 nanoparticles and their performance for the adsorptive removal of the methylene blue (MB) dye was reported. The as-produced samples and their associated calcined corresponding ones in the range of 400–800 °C were systematically characterized for their structure and microstructure using different techniques. For the expected best candidate for the MB removal, the pure NiZn nanoferrite (optimized parameters: Fuel=Urea; pH=5; [Fe3+]:0.025 M; Total nitrate to fuel molar ratio=8/6.66) consists of ultrasmall nanocrystals with an average crystallite size of ∼4 nm. For the optimization study of adsorptive removal of the MB dye by selected ultrasmall NiZn ferrite nanoparticles, various critical physicochemical parameters were varied. Regarding the effect of calcination temperature, it was demonstrated that the nanoferrite calcined at 500 °C showed the best removal efficiency of MB (for instance ∼43% and ∼72%, for the as-prepared and the nanoferrite calcined at 500 °C, respectively). For the selected nanoparticles, the removal efficiency was found to increase in a monotonous manner in the pH range of 4–11. This increase was faster with pH values higher than the pHPZC (∼8). For instance, it is ∼10% for pH∼4, ∼18% for pH∼8 and ∼62% for pH∼11. Whereas, the uptake capacity of the dye onto the produced nanoparticles was found to decrease and increase, respectively, with the increase in the dosage and in the MB concentration. Whatever the dye concentration, almost of the removable amount of the dye takes place in the first 30 s. The very fast adsorption rate observed in the initial stage was mainly attributed to the external surface properties of the ferrite nanoparticles. Additionally, for an industrial, economic and environmental purposes, the reusability efficiency of the nanoparticles was tested. The nanoadsorbent was stable for up to five adsorption–desorption–regeneration–reuse consecutive cycles without obvious decrease in the removal efficiency for dyes.